The complications of urinary lithiasis - Eckstein, Herbert B. (The Turkish Journal of Pediatrics, 1961)
The complications which occurred in a series of 119 consecutive cases of urinary lithiasis in children are described and discussed. In no less than 6% of the cases were complications present as the result of a stone, and many of these were serious. Two children died of their complications, one of anuria and one of extravasation of urine. Many of these complications could be avoided by the early diagnosis and surgical treatment of the stones.